The Influence of CO2 Saturated Brine on Microstructure of Coal: Implications for Carbon Geo-Sequestration - Li, Xiaolong; Yu, Hongyan; Lebedev, Maxim; Lu, Minghui; Yuan, Yujie; Yang, Zhen; Cheng, Wei; Chen, Sisi; Zhan, Jie; Ding, Shuaiwei; Johnson, Lukman (Frontiers in Energy Research, 2022)
Carbon dioxide geological storage in deep underground oil and gas reservoirs or coal seam is considered a key technology to effectively mitigate carbon emissions. Deep coal seams are the potential host rock for CO2 storage, with chemical reactions occurring when coal is exposed to CO2-saturated brine. However, limited studies have been conducted to reveal the effect of chemical reaction, particularly to unveil how this importantly affects the coal seam porosity at the micrometer scale. In this study, the CO2 geological storage is simulated using a high-temperature and high-pressure reactor containing CO2-saturated brine and coal samples. The samples in the previous study on the effect of CO2 on coal mostly contained high content of carbonate minerals and sulfide minerals. However, the tested Collie coal samples, which are characterized by high content of kaolinite and siderite, are rarely used. This coal was quantitatively analyzed using a scanning electron microscope before and after reaction. The results show that the microstructure of coal matrix was largely changed due to acid exposure. Kaolinite and siderite in the coal matrix were dissolved, the size and morphology of the cleats increased, and the absolute effective porosity also increased significantly. Most importantly, the connectivity of cleat network was improved, leading to an increase in CO2 storage space and coal seam permeability. Therefore, it is concluded that the microstructure changes of coal can be measured on a microscopic scale, and it is better to be quantitatively evaluated to improve the accuracy and reliability of CO2 storage in deep coal seams.